Improving English Language Learning Skills Using Social Networking - Harto Malik; Sayama Malabar; Andri Kurniawan; Husna Imro'athush Sholihah; Lela Susanty (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This paper discussed efforts to improve English learning skills using social networking. The author believes that most students now learning English as a foreign language certainly need more opportunities to practice excellently to relax their learning. However, progress in learning English is often identified with fluency in communicating with fellow students, not in terms of fluency in speaking using various social media applications so that such an atmosphere presents an open feel for students in the form of not only communicating in friendship but still looking for robust learning solutions. This review tries to describe how the benefits of social networks are not only valuable as friendships but can improve English proficiency for students in Indonesia. The data that we found was then analyzed from various sources and perspectives, which were the results of secondary data in book publications, scientific papers, and websites that discussed foreign language learning issues using social media networks. Based on the study results and discussion, we conclude that foreign language learning is like a social network. The reason is that through social media, there are now many types of social media that can be used to learn English in an effective and relaxed manner, all of which provide a variety of features and content that make learning more polite but still helpful.